2007
DOI: 10.1530/rep-07-0032
|View full text |Cite
|
Sign up to set email alerts
|

Cervical remodeling during pregnancy and parturition: molecular characterization of the softening phase in mice

Abstract: Cervical remodeling during pregnancy and parturition is a single progressive process that can be loosely divided into four overlapping phases termed softening, ripening, dilation/labor, and post partum repair. Elucidating the molecular mechanisms that facilitate all phases of cervical remodeling is critical for an understanding of parturition and for identifying processes that are misregulated in preterm labor, a significant cause of perinatal morbidity. In the present study, biomechanical measurements indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
217
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(238 citation statements)
references
References 62 publications
11
217
1
Order By: Relevance
“…The uppermost region of the endocervix is lined with columnar epithelia, and this squamocolumnar junction delineates the boundary between uterine and cervical tissue. Resident immune cells including neutrophils, eosinophils, and macrophages are present in the cervix though their localization and relative numbers change over the course of pregnancy (Timmons & Mahendroo 2006, Read et al 2007). All these cell types have specific functions during pregnancy and parturition that are in part regulated by the steroid hormone environment.…”
Section: Cervical Architecturementioning
confidence: 99%
See 4 more Smart Citations
“…The uppermost region of the endocervix is lined with columnar epithelia, and this squamocolumnar junction delineates the boundary between uterine and cervical tissue. Resident immune cells including neutrophils, eosinophils, and macrophages are present in the cervix though their localization and relative numbers change over the course of pregnancy (Timmons & Mahendroo 2006, Read et al 2007). All these cell types have specific functions during pregnancy and parturition that are in part regulated by the steroid hormone environment.…”
Section: Cervical Architecturementioning
confidence: 99%
“…Since that time, research by many investigators has confirmed that cervical remodeling is a dynamic process that begins long before the onset of uterine contractions. The cervical remodeling process can be divided into four overlapping phases termed softening, ripening, dilation, and postpartum repair (Read et al 2007). …”
Section: Cervical Architecturementioning
confidence: 99%
See 3 more Smart Citations